P4 Adverse experiences of unaccompanied asylum seeking children and the impact on their emotional wellbeing and mental health needs. (12th March 2018) - Emedo, M; Habeeb, S; Joyce, M; Anderson, S; Lorek, A
Abstract : Background: All Unaccompanied Asylum Seeking Children (UASC) entering local authority care in England must have a holistic health assessment. Within our local authority this includes history and physical examination using a standardised proforma and Strengths and Difficulties Questionnaire (SDQ). Methods: Retrospective review of records from Jan – August 2016. Recording SDQ scores, experiences of abuse and mental health difficulties. Results: 99 UASC; median age 16 (range 12–17) years, 96% male. Ten nationalities, mostly Afghani 39% or Eritrean 35%. High levels of negative life experiences; 46% had experienced the death of a close family member; 75% not in contact with any family. In addition to adversity prior to departure, 51% experienced trauma en route to the UK. 32% reported detention, 27% physical assault and 12% were tortured. Libya was most commonly named, however European countries such as Belgium, Hungary and Bulgaria were also identified as locations of abuse. SDQ scores outside the normal range for emotional distress in 37%, peer relationships in 17% and overall stress in 13%. There was a statistically significant association (Fisher's exact test; p=0.0003) between high SDQ score for emotional distress and adverse experiences during transit to the UK. 43 (43%) were identified as needing referral to mental health services. Discussion: Data from our cohort demonstrates a high burden of distress, with large numbers of UASC experiencing abuse in transit to the UK. This is significantly associated with high levels of emotional distress in our cohort. The predictable need in this population should be accounted for in planning for and increasing access to mental health services.